THE CONTRIBUTIONS OF THE CAROCOK TARUSAN FISHING PORT FOR FISHERIES SECTOR IN WEST SUMATERA PROVINCE - Dwita Nurmala; Nofrizal Nofrizal; Jonny Zain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT A series survey activities was conducted on July 9th – 17th , 2018 at Carocok Tarusan fishing port, Pesisir Selatan. The purpose of this study is to abtain data and information about contribution of Carocok Tarusan fishing port on fisheries sector in West Sumatera Province. By using survey method, the result showed that the contribution of fishing port in fisheries sector was shown number of fishing boat were1,37% - 2,05%, number of fishing gear were 1,06% - 2,12%, number of boat lift net were 6,78%-8,65%, large net 6,98%-10,68%, troll line 1,76%-2,56% and Gillnet 0,75%-1,36%, number of fisherman were 7,21% - 8,20%, number of fisheries production 4,36% - 5,49% and number of production value were 8,22% - 9,48%. Keywords :Contibution, Carocok Tarusan Fishing Port, Fishery Sector